Endodontic management of a bifid mandibular canine: A case report and focused literature update - Pandey, Pragya; Vaishnavi, Abinia; Bharti, Ramesh (Indian Journal of Case Reports, 2026)
A thorough understanding of root canal morphology is essential for successful endodontic therapy. The mandibular canine typically presents with a single root and canal; however, rare variations such as bifid roots with separate canals may occur and pose diagnostic and therapeutic challenges. Failure to recognize these variants can lead to missed canals and compromised outcomes. This report describes endodontic management of a mandibular right canine with two roots and two separate root canals in a 32-year-old female. Root canal treatment was performed under magnification using chemomechanical preparation followed by warm vertical compaction obturation. At 12 months, clinical and radiographic follow-up demonstrated satisfactory periapical healing. As a comprehensive review exists up to 2017, this report presents a focused update of later cases, enriching the limited global literature and improving clinical awareness of anatomical variations in mandibular canines.